MUSIK KONTEMPORER DI DALAM IBADAH GEREJA KARISMATIK (Suatu Kajian Historis-Musikologis) - Pranesta, Ramanda Hamran (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
The development of the church especially the music used in worship greatly evolved especially the charismatic  church. This is a familiar phenomenon and is characteristic of the charismatic  church. These characteristics can be seen from the genres of music used in accompanying worship. Or in other words the music used to be an identity in the charismatic  church that uses the existing music is no longer dependent on the music of the church as it only uses the organ or chorus only. This is indeed quite significant development, because the elements of freedom in music to be a forward factor in charismatic.  There are various types of music or musical genres used or used in accompanying worship in a charismatic  church such as; Blues Music, Jazz Music, and Rock Music. Some of these genres are not really a genre of music that is suitable and suitable for use in worship, but the use of idioms of genre that can affect the addition of worship. Once any music genre can be used in worship in a charismatic  church. There are three aspects to the msuknya music kompeller in the church kharismatik antaralain; Subject, Mediator and Congregation  (Audience). These three aspects are very very important in the development of music that is present in the charismatic  church today